NOXIOUS GASES THREAT AMINO ACIDS IN FUNAMBULUS PENNANTI - GAUTAM, R.K.; CHAUDHARY, VINEETA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
Carbon monoxide (CO) and Sulphur dioxide (SO2) are the main noxious gases present in our environment. Present histochemical observations madeonaminoacids in the testes and ovaries of common ground squirrel (Funambulus pennanti) reveal an overall depletioninthetyrosine and tryptophane after CO and SO2 exposures. These noxious gases interact with cellular proteins inspecific manner.